PENGARUH TEKANAN ANGGARAN WAKTU, LOCUS OF CONTROL, KOMITMEN ORGANISASI DAN KINERJA AUDITOR TERHADAP PERILAKU DISFUNGSIONAL AUDITOR (STUDI EMPIRIS PADA AUDITOR KANTOR AKUNTAN PUBLIK DI JAKARTA PUSAT DAN JAKARTA SELATAN) - Wanda Fitria; Kurniasih Dwi Astuti; Roni Budianto (FEB Universitas Sultan Ageng Tirtayasa, 2018)
The purpose of this study was to examine the effect of time budget pressure,the locus of control, organizational commitment, and performance auditor of auditor dysfunctional behaviors (an empirical study in public accountant firm in Central Jakarta and South Jakarta). This research used primary data collected directly from respondents. Method of determining the sample in this research was purposive sampling technique based on the consideration. Population in this researchwas the auditors who work at public accountant firm in Central Jakarta and South Jakarta.The sample in this research used 50 auditors who worked at public accountant firms registered at Institut Akuntan Publik Indonesia (IAPI) Jakarta 2017. This study tested using data quality, classic assumptiontest and linear regression analysis using SPSS for windows 23. The results of this study showed that the time budget pressure was significantly positive effect toward dysfunctional audit behavior while the locus of control was positive effect unsignificantly to dysfunctional audit behavior. And variable of organizational commitment and performance auditor were significantly negative effect to dysfunctional audit behavior.